Mycotic rumenitis in feedlot cattle - Konis, Taiel P.; Costa, Enrique F.; Francisco, Reynaldi; Quiroga, María A. (Brazilian Journal of Veterinary Pathology, 2025)
Feedlot with 3,700 animals. About 20 animals died in one month (December 2023). In January 2024, 7 new animals died within 2 days, prompting a visit to the establishment. On physical examination, clinical signs included apathy, lethargy, marked ptyalism and sialorrhea, watery diarrhea, and dyspnea with superficial tachypnea. The affected animals often adopted a kyphotic posture and refused to move when stimulated (Fig.1). Clinical signs began 15 to 45 days after arrival at the feedlot. Treatments with tilmicosin, tylosin, florfenicol, and tulathromycin were administered without a favorable response. The cattle had been fed a low-fiber, high-cereal diet containing monensin.